Ocular Manifestations of Aplastic Anemia: Rare Case of Anemic Retinopathy - Juanarta, Pieter; Ihsan, Grimaldi; Iskandar, Erwin; Kartasasmita, Arief; Virgana, Rova; Indra, Made (Indonesian Vitreoretinal Society, 2025)
Incidence of aplastic anemia was 1-2 cases per million population per years, and showed higher rate in Asia and 10-25 years old. Anemic retinopathy can occur in 28% of patient with severe anemia, especially if accompanied by thrombocytopenia. Most cases were asymptomatic, however decrease visual acuity were also commonly found caused by haemorrhage and Macular edema. A 65 years old female patient came with blurry vision ten days prior admission accompanied with loss of consciousness, recurrent bleeding from nose, gum, and bluish discoloration in her extremities four years ago. Visual acuity was 1/60 on the right eye and 0.4 log on the left eye. Funduscopic examination showed vitreous haemorrhage, dot blot, hard exudate, and tortuosity of vein. Laboratory Examination showed anemia and thrombocytopenia, and peripheral blood morphology showed normochromic anisopoikilocytosis caused by chronic disease. She was scheduled to underwent anti VEGF and showed improvement in her visual acuity after injection. Fundoscopic examination later shows sub-hyaloid haemorrhage, dot blot, hard exudate, and tortuosity of vein. She was scheduled to undergo pars plana vitrectomy and were consulted to internal medicine. Aplastic anemia is a rare disease that usually asymptomatic, thus causing late intervention and a high mortality rate. Early manifestation can be seen in retinal structure as anemic retinopathy thus ophthalmologist have valuable impact in early detection of this disease. Haemorrhage overlying the macula and macular edema is the most common cause of visual impairment. Anti VEGF treatment, transfusion of blood component, and immunosuppressive therapy is needed to prevent complication and increase patient survival rate. Patient visual acuity usually imporved after early transfusion and anti VEGF injection, however delayed intervention may cause irreversible vision loss.